Negotiation and Autonomy of the Wives of Former Convicted Terrorists - Sari, Fitria (Yayasan Jurnal Perempuan, 2018)
The discussion on terrorism is currently focused on issues concerning law enforcement efforts, cooperation between defense institutions, analysis of legal policies, and definitions of terrorism. Women (especially wives) are excluded from the process of dialogue and response to terrorism. This study emphasizes the experience and voice of the wives of former convicted terrorists. This article explores the process of upheaval and negotiation from the extremist narratives contained in the logic of thinking as a struggle in the context of self-acceptance and autonomy. This study uses a case study approach with a feminist perspective, and in-depth interviews as a method of data collection. The feminist view of Relational Autonomy and the Politics of Piety was chosen as a theoretical framework for analyzing findings. The results of the study indicate that there is an indoctrination from the husband about the teachings of extremism and that the wife experiences a struggle to internalize the teaching. On the other hand, there are also findings that show wives also negotiate with their husbands in carrying out the teachings of extremism. The conclusion of this study shows that the wife's figure experiences the process of constructivism and relational autonomy in the struggle process and its negotiations so far. In addition, the wife can also be seen as an agent to strengthen the spirit of nationalism through the values of tolerance.Â